2014
DOI: 10.2106/jbjs.m.00481
|View full text |Cite
|
Sign up to set email alerts
|

Repair Techniques for Acute Distal Biceps Tendon Ruptures

Abstract: The complication rate did not differ significantly between one and two-incision distal biceps repairs; however, the bone tunnel and cortical button methods had significantly lower complication rates compared with suture anchors and intraosseous screws. Further studies are needed to determine the optimal number of incisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 31 publications
2
91
0
14
Order By: Relevance
“…LABCN neuroapraxia was the most common complication overall (11.6% for one-incision and 5.8% for two-incision techniques); heterotopic ossification, stiffness and synostosis were more frequently reported in the two-incision technique (7.0%, 5.7% and 2.3% respectively) [17]. Grewal et al, evaluating mid-term outcomes of single and double-incision techniques reported significantly higher overall complication rate inthesingle-incision technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LABCN neuroapraxia was the most common complication overall (11.6% for one-incision and 5.8% for two-incision techniques); heterotopic ossification, stiffness and synostosis were more frequently reported in the two-incision technique (7.0%, 5.7% and 2.3% respectively) [17]. Grewal et al, evaluating mid-term outcomes of single and double-incision techniques reported significantly higher overall complication rate inthesingle-incision technique.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors sustain that complication rate does not significantly differ between one and two-incision approaches (23,9% for one-incision procedures and 25,7% for two-incision procedures) [17]. Others claim that the double-incision has significantly lower complication rates than the single-incision-approach [18].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review by Watson et al 10 showed that bone tunnel and cortical button methods resulted in significantly lower complication rates compared with suture anchor and intraosseous screw techniques. In another systematic review, Chavan et al 11 found that cortical button fixation provided higher load to failure and stiffness compared with bone tunnels, intraosseous screws, and suture anchors.…”
mentioning
confidence: 99%
“…Partial and complete ruptures are associated with pain and decreased elbow flexion and supination strength, and these are traditionally treated with open surgery [11]. Recently, all-endoscopic and endoscopicassisted techniques have been described for minimally invasive debridement of partial ruptures, and for distal biceps repair.…”
Section: Introductionmentioning
confidence: 99%